A revision of Graptophara (Hemiptera: Heteroptera: Scutelleridae) - Rédei, Dávid; Tsai, Jing-Fu (Zootaxa, 2018)
The Indomalayan genus Graptophara Stål, 1865 (Hemiptera: Heteroptera: Scutelleridae: Scutellerinae) is redescribed and revised, and its systematic position is discussed. Two species, G. reynaudii (Guérin-Méneville, 1834) (the type species, distributed in the Sundaic Region) and G. anomala sp. nov. (southern India) are recognized, redescribed or described, and illustrated. A lectotype is designated for Callidea pulchra Westwood, 1837, now a junior synonym of G. reynaudii.